2018
DOI: 10.12913/22998624/85705
|View full text |Cite
|
Sign up to set email alerts
|

Operational Properties of Anti-graffiti Coating Systems for Rolling Stock

Abstract: The article presents the comparative tests results of selected properties of anti-graffiti paint system for rolling stock industry. The measurements included an adhesion test, free surface energy, surface geometric structure, corrosion resistance and flame resistance test. The system consists of high solid corrosion protection primer, putty, filler, basecoat and anti-graffiti clearcoat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The previous tests of the paint systems showed that the first two parameters were the most difficult to fulfill, so the tests were started from this two parameters [9][10]. The tests were performed at the Materials & Structure Laboratory of the Railway Research Institute in Warsaw.…”
Section: Measurement Of Flammability Propertiesmentioning
confidence: 99%
“…The previous tests of the paint systems showed that the first two parameters were the most difficult to fulfill, so the tests were started from this two parameters [9][10]. The tests were performed at the Materials & Structure Laboratory of the Railway Research Institute in Warsaw.…”
Section: Measurement Of Flammability Propertiesmentioning
confidence: 99%
“…The test material was polarized with a potential sweep rate of 0,2 mV/s.After 24 hours electrochemical tests marked as exposed were repeated. Results are presented on Figure 5 and table 5 (Pasieczyński et al, 2018b).…”
Section: Measurementmentioning
confidence: 99%
“…It was used as the third layer from above. The thickness of the polyester putty in this system was 2000 microns [1][2][3]. Fig.…”
Section: Fire Tests For Various Materials Groupsmentioning
confidence: 99%